2021
DOI: 10.1136/bmjdrc-2020-001433
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular coupling alterations in type 2 diabetes: a 5-year longitudinal MRI study

Abstract: IntroductionRespective alterations in resting-state brain neural activity and cerebral blood flow (CBF) in type 2 diabetes mellitus (T2DM) have been reported. However, their coupling alteration in T2DM remains largely unknown.Research design and methodsTwenty-seven patients with T2DM aged 40–67 years and 36 well-matched healthy controls (HCs) underwent resting-state functional MRI (rs-fMRI) and arterial spin labeling (ASL) scans at two time points with a 5-year interval. Regional homogeneity (ReHo) and CBF wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Both of these results indicate the possibility of communication disorders between astrocytes, blood vessels and neurons, which, combined with the abovementioned processes of ROS and DAMPs production, endothelial damage, the release of inflammatory molecules, microglial activation, indicates the creation of an environment that strongly promotes NVUs dysfunction in the brain. NVC abnormalities in the brain have been detected in both an animal models of diabetes and in diabetic patients ( 171 ). The initial diabetic NVUs dysfunctions, may be a significant cause of a worsen stroke outcomes, which has been shown in several studies in experimental models of cerebral ischemia ( 150 , 172 174 ).…”
Section: The Cerebral Ischemia/reperfusion Cascade and Stroke Comorbiditiesmentioning
confidence: 99%
“…Both of these results indicate the possibility of communication disorders between astrocytes, blood vessels and neurons, which, combined with the abovementioned processes of ROS and DAMPs production, endothelial damage, the release of inflammatory molecules, microglial activation, indicates the creation of an environment that strongly promotes NVUs dysfunction in the brain. NVC abnormalities in the brain have been detected in both an animal models of diabetes and in diabetic patients ( 171 ). The initial diabetic NVUs dysfunctions, may be a significant cause of a worsen stroke outcomes, which has been shown in several studies in experimental models of cerebral ischemia ( 150 , 172 174 ).…”
Section: The Cerebral Ischemia/reperfusion Cascade and Stroke Comorbiditiesmentioning
confidence: 99%
“…Previous studies have confirmed that CBF/ReHo ratio can offer more information on local neurovascular coupling alterations in diseases (Guo et al, 2018;Liu et al, 2021;Zhang et al, 2021). In a normal brain, CBF/ReHo ratio remains balanced.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, T2DM patients with mild cognitive impairments showed increased ReHo values in the right inferior frontal gyrus (triangular part), rectus gyrus and decreased ReHo values in the right inferior temporal gyrus, left inferior occipital gyrus, middle occipital gyrus (33). Longitudinal changes of ReHo values were found in patients with T2DM, which mainly distributed in four regions including the left insula, postcentral gyrus and right rolandic operculum, precentral gyrus (34). These findings demonstrated that T2DM might lead to functional impairments in specific brain regions, contributing to cognitive impairments.…”
Section: Introductionmentioning
confidence: 95%